Phosphorus Release and Regeneration Following Laboratory Lysis of Bacterial Cells - Mine, Aric H.; Coleman, Maureen L.; Colman, Albert S. (Frontiers in Microbiology, 2021)
The availability of phosphorus limits primary production in large regions of the oceans, and marine microbes use a variety of strategies to overcome this limitation. One strategy is the production of alkaline phosphatase (APase), which allows hydrolysis of larger dissolved organic phosphorus (DOP) compounds in the periplasm or at the cell surface for transport of orthophosphate into the cell. Cell lysis, driven by grazing and viral infection, releases phosphorus-containing cell components, along with active enzymes that could persist after lysis. The importance of this continued enzymatic activity for orthophosphate regeneration is unknown. We used three model bacteria – Escherichia coli K-12 MG1655, Synechococcus sp. WH7803, and Prochlorococcus sp. MED4 – to assess the impact of continued APase activity after cell lysis, via lysozyme treatment, on orthophosphate regeneration. Direct release of orthophosphate scaled with cell size and was reduced under phosphate-starved conditions where APase activity continued for days after lysis. All lysate incubations showed post-lysis orthophosphate generation suggesting phosphatases other than APase maintain activity. Rates of DOP hydrolysis and orthophosphate remineralization varied post-lysis among strains. Escherichia coli K-12 MG1655 rates of remineralization were 0.6 and 1.2 amol cell-1hr-1 under deplete and replete conditions; Synechococcus WH7803 lysates ranged from 0.04 up to 0.3 amol cell-1hr-1 during phosphorus deplete and replete conditions respectively, while in Prochlorococcus MED4 lysates, rates were stable at 0.001 amol cell-1hr-1 in both conditions. The range of rates of hydrolysis and regeneration underscores the taxonomic and biochemical variability in the process of nutrient regeneration and further highlights the complexity of quantitatively resolving the major fluxes within the microbial loop.